Participatory planning with children: innovative experience of health promotion in higher education (Research, Society and Development, 2021)
The Unified Health System (SUS) serves the population based on the principles of universality, integrality and equality. Therefore, Health Promotion (HP) actions, as a process of empowering the community to act upon the improvement of their quality of life, are extremely important for the consolidation of SUS. Hence, this study aims to report the experience of health students, from the Federal University of Sergipe, in the application of an instrument of popular mobilization (Bambu Method), with a focus on HP, carried out with children (from 5 to 8 years old), in a school at the countryside of Lagarto-Sergipe, Brazil. Two workshops were held, attended by 26 children. It was observed encouragement to individual autonomy, aiming the consolidation of empowerment; and the awareness of the reality in which children are inserted. It also stimulated the awakening of local actors; altruism and the accomplishment of works for the collectivity. In conclusion, the manual collective work allowed the children the necessary cousciousness and autonomy to understand their social role and their importance as subjects that can make changes in the community. There were also positive effects on the professional health formation of the academics responsible for the project.